Poster 133: Validation of 3D MRI in Glenohumeral Instability Evaluation of Glenoid and Humeral Bone Loss including Glenoid Track Compared to CT Scan. Issue 7 (30th July 2022) - Liles, Jordan; Taylor, Dean; Lau, Brian; Lander, Sarah
Objectives: The objective of our study is to determine whether the addition of 3-dimensional (3D) MRI to standard MRI sequences is comparable to 3D CT scan evaluation of glenoid and humeral bone loss in glenohumeral instability. There is increasing understanding of the importance of the glenoid, as well as humeral bone loss in outcomes and surgical decision making in patients with shoulder instability. Although magnetic resonance imaging (MRI) is performed as standard of care for soft tissue evaluation of shoulder instability, CT scan remains the gold standard in bony measurements. Standard MRI evaluation has been shown to inaccurately measure bone loss. However, additional CT scans result in increased financial, time, and ionizing radiation cost to the patient. Methods: Eighteen patients who presented with glenohumeral instability were prospectively enrolled and received both MRI and CT within 1 week of each other. The MRI included an additional sequence (VIBE) which underwent post-processing for reformations (Figure 1a). The addition of a VIBE protocol, on average is an addition 4 to 4.5minutes in the scanner. CT data also underwent 3D post-processing (Figure 1b) and therefore each patient had four imaging modalities (2D CT, 2D MRI, 3D CT reformats, and 3D MRI reformats). Each sequence underwent the following measurements from two separate reviewers: glenoid defect, glenoid defect percent, humeral defect, humeral defect percentage (Figure 2a and 2b), and evaluation of glenoid track and version. Paired t-tests were used to assess differences between imaging modalities and chi squared for glenoid track. Intra-observer and inter-observer reliability were evaluated. Bland-Altman tests were also performed to assess the agreement between CT and MRI. In addition, we determined cost of each imaging modality at our single institution. Results: 3D MRI measurements for glenoid and humeral bone loss measurements were comparable to 3D CT (Table 1). There were no significant differences for glenoid defect size and percentage, or humeral defect size and percentage (P>0.05) (Table 2). Bland-Altman analysis demonstrated strong agreement with small measurement errors for 3D CT and 3D MRI percentage glenoid bone loss. There was also no difference in evaluation for determining on vs off track between any of the imaging modalities. Inter- and intra-rater reliability was good to excellent for all CT and MRI measurements (r >= 0.7). Conclusions: 3D MRI measurements for bone loss in glenohumeral instability through utilization of VIBE sequence were equivalent to 3D CT. At our institution, the costs of MRI with 3D reconstruction was 1.67x cheaper than MRI and CT with 3D reconstructions. 3D MRI may be a useful adjuvant to standard MRI sequences to allow concurrent soft tissue and accurate assessment of glenoid and humeral bone loss in glenohumeral instability. Figure 1a. (3D MRI glenoid reformation) and lb (3D CT glenoid reformation): Glenoid measurement for 3D reconstruction of MRI and CT using sagittal en face of the glenoid. A circle was placed over the inferior portion of the glenoid using margins as a guide for the circle. The glenoid height line (blue) runs from the supraglenoid tubercle to the medial aspect of the inferior base. Glenoid bone loss size (orange) and circle diameter (green) was quantified with glenoid height line marking the center of the circle. Percent glenoid bone loss was determined as [(glenoid bone loss size/circle diameter)* 100]. Glenoid track was determined through equation [(0.83 * circle diameter) - glenoid bone loss size] Figure 2a. (2D CT) and 2b (3D CT): 2a: Measurement of Hill Sachs maximal defect on axial 2D CT recorded in mm. 2b: Measurement of humeral defect percentage from the 3D reformats using sagittal projection with best fit circle. A line (blue) was placed to determine maximal humeral head height (A) then perpendicular line (green) to measure residual humeral head (B) and therefore bone defect (A-B)(orange). Percent bone loss was determined through [(A-B)/A)*100] Table 1: Mean 2D and 3D CT and MRI measurements Table 2: Paired t-test Glenoid and Humeral Bone Loss Measurements.